The use of instructional technology in teaching: a comparative analysis - Mohamed, Abdul Latheef; Afshari, Mojgan; Ghavifekr, Simin; Siraj, Saedah; Razak, Ahmad Zabidi Abdul (2013)
The current computer-based instructional technologies found in schools around the world provide enormous opportunities for teachers to use them for effective and efficient lesson delivery. This study was aimed at comparing the level of computer use for teaching purposes by business and science stream teachers in the secondary schools of Maldives. A descriptive research methodology was conducted to collect data for this quantitative study. A survey questionnaire was administrated to 85 participants (43 business teachers and 42 science teachers). The findings of this study indicate that science stream teachers have higher level of computer use for teaching purposes in comparison with business stream teachers. An independent sample t-test analysis indicated that there is no significance in the perceived support for computer use between business and science stream teachers. To increase technology use for teaching purposes and decrease the differences between two groups of teacher, training programs need to be carried out separately to meet the training needs of the each group of teachers.